“Lusofonia” sem “Lusofilia”: O caso do antigo Estado da Índia – Défice de reciprocidade cultural - Souza, Teotónio R. de (2009)
It is generally little known today that Goans produced a wide range of publications in Portuguese, in English, in French, besides their native languages Konkani and Marathi. One needs to consult the 3 volumes of Dicionário da Literatura Goesa by Aleixo Manuel da Costa, edited recently by Instituto Cultural de Macau to get an idea of the literary production of the Goans. This literary production does not permit us to conclude that Goans who wrote in Portuguese were lusophiles, or those who wrote in English were anglophiles, and so on. If Portuguese language failed to win over the hearts and minds of most Goans it was largely because Portuguese language was seen as an instrument of colonial domination